2017
DOI: 10.3892/etm.2017.5092
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of stemonine on particulate matter 2.5‑induced chronic obstructive pulmonary disease in mice

Abstract: Abstract. Particulate matter 2.5 (PM 2.5 ) is a growing concern worldwide due to its association with respiratory diseases, including chronic obstructive pulmonary disease (COPD). Stemonine, a traditional Chinese herb, has been demonstrated to exhibit anti-inflammatory and antioxidant properties, making it a potential drug for the treatment of respiratory diseases. The therapeutic effects of stemonine on mice with PM 2.5 -induced COPD were investigated in the present study. Kunming mice were randomly divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(33 reference statements)
0
8
1
3
Order By: Relevance
“…This study found that plant-derived aesculetin attenuated uPM 10 -induced oxidative stress and inflammation, accompanying reduction of neutrophilia and lymphocytosis in BALF. Antioxidants may alleviate the adverse effects of PM on chronic diseases [ 19 , 24 , 25 ]. Aesculetin attenuates alveolar injury and fibrosis induced by macrophage-derived inflammation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study found that plant-derived aesculetin attenuated uPM 10 -induced oxidative stress and inflammation, accompanying reduction of neutrophilia and lymphocytosis in BALF. Antioxidants may alleviate the adverse effects of PM on chronic diseases [ 19 , 24 , 25 ]. Aesculetin attenuates alveolar injury and fibrosis induced by macrophage-derived inflammation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since PM is associated with inflammatory respiratory diseases, including chronic obstructive pulmonary disease (COPD) and asthma, potential nutrients and supplements with an anti-inflammatory property have been suggested for their prevention and treatment [ 22 , 23 ]. For example, stemonine, a traditional Chinese herb, reduces lung inflammation in mice with PM 2.5 -induced COPD, providing a novel approach for the treatment of PM2.5-induced respiratory diseases [ 24 ]. In addition, the harmful effects of PM on respiratory diseases may be ameliorated by safe and effective natural antioxidants [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few studies on lung disease induced by PM. Although some animal model experimental studies conducted sporadically for respiratory diseases induced by PM have demonstrated the mechanisms and effectiveness of herbal medicine [17][18][19][20];…”
Section: Registration Numbermentioning
confidence: 99%
“… [53] Intranasal instillation The therapeutic effects of stemonine on mice with PM 2.5 -induced COPD were investigated in the present study. [54] Intranasal instillation To test our hypothesis that cardiovascular diseases associated with sulphur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), or PM 2.5 exposure are the result of increased heart rate (HR), decreased blood pressure (BP) and enhanced systemic inflammation. [55] Intratracheal instillation The aim of the present study was to evaluate the effects of PM 10 on electrocardiogram (ECG) parameters, blood pressure, lipid peroxidation (MDA), xanthine oxidase, and antioxidant enzyme in healthy rats and also to examine the protective effects of vanillic acid (VA) in this respect.…”
Section: Datamentioning
confidence: 99%